Efek Peningkatan Kemampuan Usaha di Kota Solok - Nirwana, Ida; Nurhayati, Nurhayati; Kurniawan, Zikri Aulya (Universitas Sang Bumi Ruwa Jurai, 2024)
Currently, there is a high expectation for young people to develop an entrepreneurial spirit, not only to become workers but also to create jobs for their local community. Therefore, we need to equip young entrepreneurs with entrepreneurial knowledge and enable them to learn about various business fields, leveraging their talents and pursuing businesses they are passionate about. The purpose of this study was to determine how improving the capabilities of young entrepreneurs in Solok City has an impact. This study employs a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The data collected in this study were qualitative, and qualitative descriptive methods were used to analyze them. This study utilized 15 informants, including heads of departments and members of institutions from the Investment and One-Stop Integrated Service Office of Solok City. The findings demonstrated that the Investment and One-Stop Integrated Service Office of Solok City's young business training program,